Pendampingan Guru dalam Pengembangan dan Penerapan Media Pembelajaran Interaktif Mata Pelajaran SKI di MI Miftahussalam, Ponorogo - Umma Fatayati; Syarifah .; Rindang Diannita; Muhammad Kafil Al-Fathin; Fayshal Karan Athilla; Dziffar Janwarko Tio Sutrisno; Ahsanu Amala Tohir; Zaid Ja’far Abdullah; Latiful Aziz Fauzi; Farid Nugraha Putra; Ahmad Muzakki Maulana; Muhammad Muflih Fathin; M. Farhan Alghalbi (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
The teaching of Islamic Cultural History (Sejarah Kebudayaan Islam/SKI) in Madrasah Ibtidaiyah faces several challenges, including the limited use of learning media, inadequate integration of educational technology, and low student participation during classroom activities. These conditions often result in teacher-centered learning practices that are less responsive to the needs of students in the digital era. In addition, many teachers still require support in developing and utilizing interactive learning media to create more engaging and effective learning experiences.This community service program aimed to enhance teachers’ competencies in designing interactive learning media, facilitate the implementation of flashcards and educational posters in SKI instruction, and evaluate their impact on student participation and learning outcomes.The program was conducted using a Participatory Action Research (PAR) approach, which actively involved teachers in identifying problems, planning activities, implementing actions, and conducting evaluation and reflection. Data were collected through classroom observations, pre-tests, post-tests, and documentation. The collected data were analyzed using descriptive quantitative and qualitative methods by calculating mean scores, percentage improvements in learning outcomes, and interpreting students’ learning activities during the implementation process.The results demonstrated that the use of interactive learning media significantly improved the quality of SKI learning. The average score of Grade V students increased from 55.90 to 80.05, while Grade VI students’ average score improved from 58.71 to 81.29. Student participation was categorized as very good, reaching 85.83% in Grade V and 89.22% in Grade VI. Furthermore, the program enhanced teachers’ abilities to develop innovative learning media, contributing to increased student engagement and improved learning outcomes.